O diálogo perante a fragmentação na Universidade. Uma alternativa para a Responsabilidade Social - López Espinosa, Raúl Homero (Universidad Nacional del Litoral, 2019)
The University Social Responsibility (USR) involves approaches to understanding complex problems from a holistic view. Under these circumstances, a combination of learning communities to build collective intelligence and horizontal structures in universities are required. This indicates the need for an approach to address the problem of fragmentation in the university management and, particularly, the various perceptions of cross–disciplinary themes such as gender, interculturality, sustainability, among others. In this context, the University of Veracruz (UV) launched the Transversa Program during the administration 2013–2017. After an evaluation in the Educational Model, a similar problem was evidenced. Therefore, Transversa aims to provide cross–disciplinary issues, under a systemic vision, in the functions of the University, and its strategy is building a culture of dialogue. This paper will give an account of this culture in light of the fragmentation and the USR.